Improving the Fine Motor Skills of Intelligence Impaired Children Through Cutting and Paste Activities with Worksheets at SLB Solokuro Lamongan - Ameiliana Dwi Siroh Putri; Budi Susetyo; Riksma Nurahmi Rinalti Akhlan (INCLUSIVE EDUCATION, 2022)
This research was conducted to develop the fine motor skills of a child with Intelligence Impaired in grade I at SLB Solokuro, Lamongan Regency through cutting and pasting pictures using worksheet media. This study aims to prove that worksheets can be used as a medium to improve the fine motor skills of Intelligence Impaired Children . The method used in this study uses a single subject research (SSR) with an A-B-A design. Measuring and collecting data on baseline conditions (A1), providing intervention (B) with worksheet media, and baseline conditions (A2). Variable measurement using the percentage of the number of instrument items. The results showed an increase in fine motor skills cutting and sticking, where initially the baseline condition (A1) at the first and second meeting was 25%, 25%. The first to fourth interventions (B) were 33.3%, 50%, 58.3%, 62.5% and at baseline (A2) 83.3%, 83.3%. Based on these results, it shows that the worksheet is effectively used as a medium in cutting and pasting activities to improve the fine motor skills of Intelligence Impaired Children.